Management - Chuck Williams (South-Western College Pub., 2007)
MANAGEMENT, 4th edition by Chuck Williams presents management theory and applications in an engaging narrative style that students will find both enjoyable and illuminating. Williams focuses on the most important management theories and concepts, enhancing and illustrating them with detailed examples and stories that pull students into the reading. Drawing from his experience as an award winning educator, Williams believes that students understand and retain information when it is personally relevant and he includes innovative features that bring all the concepts together. Throughout the text the focus is on two key themes: how managers and organizations make things happen and what really works in today's workplace. Instructors and readers praised the first three editions for their innovative approach and tools that make management both relevant and interesting-the Fourth Edition continues and improves upon this foundation of innovation